Carers' views on patient self‐care in chronic heart failure. Issue 1 (January 2016) - Cameron, Jan; Rhodes, Kerryn L.; Ski, Chantal F.; Thompson, David R.
Abstract : Aims and objectives: To examine carers' views on patient self‐care in chronic heart failure (CHF). Background: Self‐care, a key strategy in the long‐term management of CHF, can be complex and difficult to master. Carers play a key role in supporting patients in self‐care, yet their views on it are rarely sought. Design: A qualitative approach was adopted with a purposeful sample of carers of patients with CHF residing in Australia. Methods: Carers who identified themselves as providing informal care to a person diagnosed with chronic heart failure were interviewed about their views on patient self‐care. Data were collected by face‐to‐face interviews with a semi‐structured interview guide. Qualitative content analysis of the interviews was undertaken by two nurses and one psychologist. Results: Four key themes were identified pertaining to CHF patient self‐care: hindrance to engagement; roles and relationships; social support and community engagement and competency. Most carers viewed patients' fatigue and inactivity, mood and coping, and memory loss as major challenges to engagement in self‐care. They viewed emotional support and encouragement, independence and organised routines as important aspects of their relationship with the patient and as facilitators of self‐care, but also required for themselves support from their families, communities and healthcare professionals. They also viewed patient and carer experience and knowledge as being essential to successful self‐care. Conclusion: Carers viewed self‐care as an important issue for patients with CHF and indicated that they could play an enhanced role with the provision of better support and knowledge from their families, communities and health care professionals. Relevance to clinical practice: Carers are closely involved in supporting patients in CHF self‐care, even though their views are rarely considered in the organisation and delivery of heart failure management programmes. Therefore, their important contribution should be acknowledged and supported in contemporary heart failure health services.